2017
DOI: 10.3389/fnins.2017.00190
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Neurogenesis as an Adaptive Metabolic Mechanism

Abstract: In the adult brain, well-characterized neurogenic niches are located in the subventricular zone (SVZ) of the lateral ventricles and in the subgranular zone (SGZ) of the hippocampus. In both regions, neural precursor cells (NPCs) share markers of embryonic radial glia and astroglial cells, and in vitro clonal expansion of these cells leads to neurosphere formation. It has also been more recently demonstrated that neurogenesis occurs in the adult hypothalamus, a brain structure that integrates peripheral signals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 44 publications
0
31
0
2
Order By: Relevance
“…However, the physiological role of NPC proliferation within the hypothalamic stem cell niche in long-term body weight homeostasis including control of feeding and energy balance is intensively discussed in the recent literature. 8,47,48,51,63 In this concept, proliferation of NPCs-mainly NSCs located within the lateral hypothalamus, which are inhibited by NE signaling in our studies-is associated with body weight loss or maintenance, while proliferation of medio-basal NPCs appears to be associated with weight gain. The actions of NE on periventricular neurogenesis are in contrast to its effects on hippocampal neurogenesis with its stimulatory role on NPC proliferation within the SGZ of the dentate gyrus (our study and those of others 14,15 ).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…However, the physiological role of NPC proliferation within the hypothalamic stem cell niche in long-term body weight homeostasis including control of feeding and energy balance is intensively discussed in the recent literature. 8,47,48,51,63 In this concept, proliferation of NPCs-mainly NSCs located within the lateral hypothalamus, which are inhibited by NE signaling in our studies-is associated with body weight loss or maintenance, while proliferation of medio-basal NPCs appears to be associated with weight gain. The actions of NE on periventricular neurogenesis are in contrast to its effects on hippocampal neurogenesis with its stimulatory role on NPC proliferation within the SGZ of the dentate gyrus (our study and those of others 14,15 ).…”
Section: Discussionmentioning
confidence: 59%
“…47 This parenchymal hypothalamic neurogenesis has been reported to be regulated by several cytokines or neurotrophic factors as well as by specific neurodegenerative events and dietary signals. 47,48 The relationship between these parenchymal hypothalamic NPCs and those of the hypothalamic ventricular zone remains unclear, but might be similar to other brain regions with ventricular NPCs (tanycytes in the hypothalamus) might give rise to parenchymal NPCs. 49,50 However, our results provide strong evidence that NE acts as an endogenous negative regulator of the hypothalamic periventricular stem cell niche, with no or only minor effects on ependymal tanycytes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, due to their localization in the hypothalamus, tanycytes are in a privileged position to detect hormonal, nutritional and mitogenic signals released by peripheral organs or present in the CSF. Recent studies reveal that in response to nutritional signals, tanycytes are capable of differentiating into anorexigenic neurons (Gouaze et al, 2013; Recabal et al, 2017), which strongly supports the notion that these cells are involved in the control of feeding behavior.…”
Section: Discussionmentioning
confidence: 76%
“…GLUT2 was found in neurons and astrocytes dispersed in many structures, including the hypothalamus, the brain stem, the thalamic area (Arluison, Quignon, Thorens, Leloup, & Penicaud, 2004; Labouebe, Boutrel, Tarussio, & Thorens, 2016) and in tanycytes (Garcia et al, 2003). Tanycytes are radial glial‐like cells surrounding the lateral walls of the infundibular recess (Recabal, Caprile, & Garcia‐Robles, 2017). Their apical poles contact the cerebrospinal fluid (CSF), and basal extensions project into the arcuate nucleus (AN) (Flament‐Durand & Brion, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Although several mechanisms, such as changes in firing activity or in gene expression profiles can be affected, altered neurogenesis is another possible mechanism because ΔFosB was previously shown to increase dendrite spine plasticity, which serve to increase the number of possible contacts between neurons. Indeed, cumulative research over the past two decades demonstrated that neurogenesis occurs in adult human and mouse hypothalamus and is subject to regulation by dietary and other factors . Therefore, to determine whether ΔFosB affected neurogenesis in our experimental models, primary hypothalamic neurons were isolated from adult NPY‐CRE and CART‐CRE mice, infected with CRE‐inducible AP1 factor LVs, thereby targeting only NPY‐producing or CART‐producing neurons in vitro, and neurite regeneration from neurospheres was monitored.…”
Section: Resultsmentioning
confidence: 99%